Report on the Beveridge proposals
1943-01-19 1943 1940s 20 pages 9. Price Level. 13. We would make certain general observations on the plan as we see it. In the first place, Sir William Beveridge bases his calculations on an increase in prices of 25% over the pre-war level. This, we think, is too optimistic, even on the assumption that the wisest financial policy is followed in the years immediately after the war. National Income. Secondly, it should be noted that the plan assumes an ever increasing national income, and though we have every confidence in the future, there are certain elements of doubt in this regard. Taxability of Citizens. Thirdly, we would draw attention to the heavier burden which would be placed upon contributors. Each contributor would be called upon to pay up to £11 a year, and this is a substantial tax which may well lead to a demand from the wage-earning community for raising exemption rates for Income Tax. We are strongly of the view that it is essential to retain within the scope of Income Tax the great majority of wage-earners. Moreover, in view of the very wide re-distribution of income, it is clear that our national expenditure cannot otherwise be met. Unlimited Liability of State. Fourthly, the plan is one involving limited contributions by employers and workers and a contract of unlimited liability for the State. Is the State justified in assuming a liability of this kind to meet not only want but also to assure benefits to those not in need? Much of this objection would disappear and the principle of insurance be more clearly established if the liability of the State was to add a fixed proportion of the contributions coming from others. Benefits in excess of those which would be so available would have to come through the medium of Assistance with a personal needs test. 200/B/3/2/C216/5/93